Review of domestic and international financial security - Lian-peng LI; Hong LUO (网络与信息安全学报)
Based on financial informatization, financial information security concept, current major risks to financial information security in domestic and international were overviewed and summarized, including network security, data security and business & services continuity, etc. Some effective techniques and control measures in this areas were introduced. Finally, relevant implications and recommendations were proposed.